Enriched Environment Promoted Cognitive Function via Bilateral Synaptic Remodeling After Cerebral Ischemia - Wang, Chuanjie; Zhang, Qun; Yu, Kewei; Shen, Xueyan; Wu, Yi; Wu, Junfa (Frontiers in Neurology, 2019)
Ischemic stroke is the second leading cause of death worldwide. Ischemia-induced cognitive dysfunction may result in a poor quality of life. Synaptic plasticity plays a key role in cognition promotion. An enriched environment, which can attenuate cognitive deficits in chronic cerebral hypoperfusion, has been shown to facilitate synaptic plasticity. However, the effect of enriched environment on synaptic plasticity in bilateral cerebral hemispheres in stroke remains unclear. This study used a permanent middle cerebral artery occlusion mouse model, which was divided into standard-housing and enriched-environment groups. The Morris water maze test was performed to detect the cognitive function. Electron microscopy was used to determine the synapse numbers. The expression of SYN and GAP-43 was then quantified by immunofluorescence staining and Western blot analysis. Compared with the standard housing, enriched environment promoted the cognitive function recovery in the mice with stroke. Moreover, enriched environment increased the synapse numbers and the expression of SYN and GAP-43 in both the ipsilateral and contralateral hemispheres (P < 0.05). A further correlation analysis revealed a positive correlation between the cognitive function outcomes and the relative expression of GAP-43 and SYN. Further, the correlation of the expression of GAP-43 and SYN with cognitive function was higher in the contralateral brain than in the ipsilateral brain. In conclusion, an enriched environment may promote cognitive function via bilateral synaptic remodeling after cerebral ischemia. Also, the contralateral brain may play an important role in the recovery of cognitive function.